Excavation assessment in wet tropically sedimentary rock - Liang, Maybelle (Penerbit UTM Press, 2015)
The selection of suitable methods to be employed for surface excavation works is particularly important in geotechnical engineering projects. Factors such as environmental constrains, rock properties and size of site may affect the selection of machine required for surface excavation. Wrong selection of equipment and technique can result in unrecoverable expenses and thus, should be avoided. Great challenges in excavation works are expected in sedimentary rock where the occurrence of discontinuity such as bedding thickness, foliation and the inhomogeneity of rock as well as effect of moisture can greatly affect its excavatability. This paper aims to identify and highlight the factors affecting the excavation works in wet tropically weathered sedimentary area as what have been experienced in Malaysia. Some of these factors, however, are not specified in the existing general excavatability assessments. Assessment by practical excavation was carried out at three sedimentary rock sites in Nusajaya, Malaysia, taking into account the related parameters. Statistical analysis by using SPSS was then being conducted in order to determine the correlation of each parameter with productivity of excavation and their significance in affecting the excavatability.Based on the results obtained, it was found that the parameters such as Is50, R, UCS, density, ITS, Js, JL, Jd, IP and moisture content play significant roles in affecting the excavatability of sedimentary rocks. Meanwhile, the existence of bedding, Id2 and Jn are deemed to be neglected. It is believed that this study can help to enhance the knowledge on factors that complicate the excavation works in sedimentary areas